Hanseniaspora uvarum from Winemaking Environments Show Spatial and Temporal Genetic Clustering - Albertin, Warren; Setati, Mathabatha E.; Miot-Sertier, Cécile; Mostert, Talitha T.; Colonna-Ceccaldi, Benoit; Coulon, Joana; Girard, Patrick; Moine, Virginie; Pillet, Myriam; Salin, Franck; Bely, Marina; Divol, Benoit; et al. (Frontiers in Microbiology, 2016)
Hanseniaspora uvarum is one of the most abundant yeast species found on grapes and in grape must, at least before the onset of alcoholic fermentation which is usually performed by Saccharomyces species. The aim of this study was to characterise the genetic and phenotypic variability within the H. uvarum species. One hundred and fifteen strains isolated from winemaking environments in different geographical origins were analysed using 11 microsatellite markers and a subset of 47 strains were analysed by AFLP. H. uvarum isolates clustered mainly on the basis of their geographical localisation as revealed by microsatellites. In addition, a strong clustering based on year of isolation was evidenced, indicating that the genetic diversity of Hanseniaspora uvarum isolates was related to both spatial and temporal variations. Conversely, clustering analysis based on AFLP data provided a different picture with groups showing no particular characteristics, but provided higher strain discrimination. This result indicated that AFLP approaches are inadequate to establish the genetic relationship between individuals, but allowed good strain discrimination. At the phenotypic level, several extracellular enzymatic activities of enological relevance (pectinase, chitinase, protease, β-glucosidase) were measured but showed low diversity. The impact of environmental factors of enological interest (temperature, anaerobia and copper addition) on growth was also assessed and showed poor variation. Altogether, this work provided both new analytical tool (microsatellites) and new insights into the genetic and phenotypic diversity of H. uvarum, a yeast species that has previously been identified as a potential candidate for co-inoculation in grape must, but whose intraspecific variability had never been fully assessed.